KELIMPAHAN POPULASI, PREFERENSI DAN KARAKTER KEBUGARAN MENOCHILUS SEXMACULATUS (COLEOPTERA: COCCINELLIDAE) PREDATOR KUTUDAUN PADA PERTANAMAN CABAI - Novri Nelly (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2012)
This predator is efective to control population of aphids, so the aim of research was to study the field population abundance, predator preference to this prey, and fitness character of M. sexmaculatus as predator. The population fluctuation was observed at conventional and organic farming. The preference test was conducted by choice and no choice test for some types of prey. Fitness test was performed by studying its prey, the number of eggs produced and number of eggs hatched. The results showed that M. sexmaculatus population abundance was fluctuated, the abundance higher in chili cultivated conventionaly than cultivated in organic farming. But in conventional farming decreased with increasing age of chili. Preference test showed that almost all species of aphids preferred by M. sexmaculatus. Some prey species found were aphids, thrips and Neotoxoptera. Predator fitness levels showed by the longevity of females ranged 9-10 days. Oviposition period was on average five days, while the post-oviposition was two days. The number of eggs produced ranged 100-200 eggs with an average of 135.3 eggs.